Impact of evaporation parameter on quality of solution to travelling salesman problem by ant colony optimization algorithm - Míča Ondřej (My University, 2015)
Ant colony optimization is metaheuristic algorithm inspired by nature. It has several parameters, which have to be set before the first run of algorithm and their correct setting is important for finding a satisficing solution. In this paper, it is shown how different value of one of these parameters – the evaporation factor – can affect the quality of given solution.
Vliv koeficientu odpařování na kvalitu řešení problému obchodního cestujícího metodou mravenčí kolonie
Keywords: Ant colony optimization; Metaheuristic; Optimization; Travelling salesman problem; Metoda mravenčí kolonie; Metaheuristické metody; Optimalizace; Úloha obchodního cestujícího